Ossifying fibromyxoid tumor- a case report - Liaquat, Ahmad; Naseer, Rabia; Riaz, Nabeela; Ul Haq, Ehsan (Journal of Chitwan Medical College, 2021)
Ossifying fibromyxoid Tumor (OFMT) is a neoplasm of varying histopathology; it is rare and affects males of middle age. It has an intermediate malignancy potential (rarely metastasizing). The clinical picture of OFMT presents as a slowly expanding mass, which arises from subcutaneous tissue and is not fixed to underline bone. Presented here is a case of eleven years old female presented with a chief complaint of aesthetically unpleasing, slowly enlarging painless mass on the right side cheek of the face.